Minimal factor XIII activity level to prevent major spontaneous bleeds. (17th August 2017) - Menegatti, M.; Palla, R.; Boscarino, M.; Bucciarelli, P.; Muszbek, L.; Katona, E.; Makris, M.; Peyvandi, F.
Abstract : Essentials A strong association between bleeding severity and FXIII activity level (FXIII:C) was shown. The range 5–30 IU dL −1 of FXIII:C was associated with a high variability of bleeding severity. The PROspective study confirmed the association between FXIII:C activity and bleeding severity. A FXIII:C of 15 IU dL −1 is a proposed target to start prophylaxis for prevention of major bleeding. Summary: Background: Congenital factor XIII (FXIII) deficiency is a rare bleeding disorder associated with significant bleeding manifestations. The European Network of Rare Bleeding Disorders (EN‐RBD) study, performed from 2007 to 2010, showed a strong association between bleeding severity and FXIII activity in plasma of patients with FXIII deficiency. Among these patients, variable levels of FXIII activity, from undetectable to 30%, were associated with a wide range of bleeding severity. Objectives and patients: The present cross‐sectional study, in the frame of the PRO‐RBDD project, a prospective cohort study, analyzed data of 64 patients with FXIII deficiency and different types of clinical and laboratory severity. Results: The results of this analysis confirmed that FXIII coagulant activity in plasma is well associated with clinical severity of patients. In addition, 15 IU dL −1 of FXIII activity was identified to be the level under which the probability of spontaneous major bleeding sharply increases (from 50% for levels of 15 IU dL −1 to more than 90% for levels of 5 IU dL −1 or lower). Conclusion: The PRO‐RBDD study suggests a FXIII coagulant activity level of 15 IU dL −1 as a target to start prophylaxis in order to prevent major bleedings, such as central nervous system or gastrointestinal tract hemorrhages.